Legitimacy Ethnographic and Theoretical Insights - Pardo, Italo; Prato, Giuliana B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Global in scope, this original and thought-provoking collection applies new theory on legitimacy and legitimation to urban life. An informed reflection on this comparatively new topic in anthropology in relation to morality, action, law, politics and governance is both timely and innovative, especially as worldwide discontent among ordinary people grows. The ethnographically-based analyses offered here range from banking to neighbourhoods, from poverty to political action at the grassroots. They recognize the growing gap between the rulers and the ruled with particular attention to the morality of what is right as opposed to what is legal. This book is a unique contribution to social theory, fostering discussion across the many boundaries of anthropological and sociological studies.
1. Introduction: Methodological and Theoretical Issues of Legitimacy -- 2. On the Legitimacy of Political Representation: Institutional Adaptations to Challenges from Urban Europe -- 3. A Conundrum of Democracy: Naples as a Test Case of Governance that Lacks Legitimacy -- 4. Unemployment, Urban Poverty and Political Legitimacy: The Dark Side of Governance -- 5. Legal but not Legitimate: Changing Practices of Financial Citizenship in Turkey -- 6. Changing Ideas of Legitimacy in Neighbourhoods: Reflections from a Town in Kerala -- 7. Privatization of Urban Governance and the Disputes for Legitimacy in a Social Housing Megaproject in Soacha, Colombia -- 8. In or Out? Claims and Practices of Legitimacy in Urban East Africa -- 9. Undermining Governmental Legitimacy at the Grass Roots: The Role of Failed Promises and Inflated Expectations of Community Accountability -- 10. Detachment and Commitment in the Competing Claims of Legitimacy Surrounding the Ephemeral Opposition to the Redesign of VigerSquare, Montreal, Quebec -- 11. Citizenship and Legitimacy in India: Kolkata's Anglo-Indian Experiences -- 12. Morality, Ethics and Legitimacy: The Roma and their Legitimization of Power Relations in Everyday Life -- 13. Conflicting Loyalties and Legitimate Illegality in Urban South Lebanon -- 14. Mourning Through Protest in Seoul: Debates over Governance, Morality and Legitimacy after the Sewŏl Ferry Disaster -- 15. Legitimacy and Urbanities: Utilising the Durkheimian Perspective.
Keywords: Ethnology; Political science; Political sociology; Ethnography; Sociocultural Anthropology; Governance and Government; Political Sociology